2018
DOI: 10.3126/jonmc.v7i2.22289
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Amplitude of Accommodation and its Relation to Errors of Refraction: A Hospital Based Study

Abstract: Background: The unique ability of the eye to vary the refractive power of the lens and to focus on things at a range of distances is called accommodation. The reduction of this ability in which the near point recedes further away from comfortable reading distance is called presbyopia. There is continuing research to understand this process and correct this affliction that affects each and every person at the peak of their productive life. With an aging population, the proportion of people above 40 years is on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This finding of our study can be attributed to the existing knowledge of the effect of age on the amplitude of accommodation and the onset of presbyopic symptoms. 10,11 The onset of presbyopia depends not only on age but also on the refractive status of the individuals, their reading habits, and near work. Hypermetropes start in life with a near point considerably farther away than that of an emmetrope, or a myope therefore subjects with hypermetropia may show presbyopic symptoms at an early age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding of our study can be attributed to the existing knowledge of the effect of age on the amplitude of accommodation and the onset of presbyopic symptoms. 10,11 The onset of presbyopia depends not only on age but also on the refractive status of the individuals, their reading habits, and near work. Hypermetropes start in life with a near point considerably farther away than that of an emmetrope, or a myope therefore subjects with hypermetropia may show presbyopic symptoms at an early age.…”
Section: Resultsmentioning
confidence: 99%
“…This finding of our study was well supported by studies done elsewhere which concluded that corrected hypermetropes will need near addition at a younger age due to lower effective accommodation, and hypermetropes are symptomatic earlier than myopes. [9][10][11] The study was conducted in a tertiary care hospital of central Nepal over a long period of time, and with a good sample size. The study has its own limitations as it only covered the age group of 30-60 years.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal evolution is an imperative dimension of AA measurements. Speci cally, numerous studies focused on quantifying AA reported a linear decrease in AA with age [1,5,10,11,19,47,51,64,67,88].…”
Section: Introductionmentioning
confidence: 99%